Electrical properties of lanthanum doped Bi4Ti3O12 thin films annealed in different atmospheres - Simoes, A. Z.; Ries, A.; Stojanovic, B. D.; Biasotto, G.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
Pure-and lanthanun doped Bi4Ti3O12 thin films were deposited on Pt/Ti/SiO2/Si substrate using a polymeric precursor solution. Annealing in static air and oxygen atmosphere was performed at 700 degrees C for 2 h. The obtained films were characterized by X-ray diffraction and atomic force microscopy. The dielectric constant and dissipation factor were measured in the frequency region from 1 kHz to 1 MHz. Electrical characterization of the films pointed to ferroelectricity via hysteresis loop. Films annealed in static air possess a dielectric constant higher than films annealed in oxygen atmosphere due to differences in the grain size, crystallinity and structural defects. A regularly shaped hystereses loop is observed after annealing in static air. The obtained results suggest that the annealing in oxygen atmosphere can increase the trapped charge and the relaxation phenomenon. (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: bismuth compounds; crystal structure; ferroelectric materials